Performance Analysis of Step Down Type-Transformator of Factories at the Company of Surya Toto Indonesia Cikupa - Dannisa Deza Azkia; Irwanto . (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2020)
Transformer is an electrical device used to transform power or electrical energy from high voltage to low voltage or vice versa, through a magnetic coupling and based on the principle of electromagnetic induction.  Transformers are widely used, both in the electric and electronic fields.  The use of transformers in power systems allows the selection of appropriate and economical voltages for each purpose so that the transformer is a very important component in the distribution of electric power from distribution substations to consumers. Keyword: Performance, Trafo, Step Down, FactoryDOI : http://dx.doi.org/10.23960/jpvti.v2.i1.202002